Tinjauan faktor-faktor yang mempengaruhi komitmen pekerja terhadap organisasi. - Zainal Abiddin, Norhasni; Ismail, Noralai (2010)
Commitment in the individual behavior context is a strong desire to stay in an organization. Commitment has been identified as an important factor to determine the success and overall effectiveness of an organization. The objective of this article is to review the literature on factors which influenced employee commitment. The result shows that factors such as supervisor, job interest, colleague and salary were contributed to employee commitment. This article also identifies the relationship between demographic factors towards commitment. Among others, age, gender, salary and tenure have been identified as factors which contributed to employee commitment. Besides, this article reviews motivational theories and their relationship with employee commitment. Therefore, it is hoped that this article could give general view in the aspects of employee commitment towards an organization.